Evaluation of the Primary School Literacy Movement Program in the Selayar Islands - Dewi Indrawati; Kaharuddin Arafah; Patahuddin Patahuddin (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This research aims to evaluate the implementation of the School Literacy Movement (GLS) program in elementary schools in the Selayar Islands. The focus of the research includes aspects of planning, implementation, supporting facilities, participation of school community members, and the impact of the program on improving the literacy culture of students. The research uses a descriptive evaluative approach with the CIPP model (Context, Input, Process, Product). The research subjects consisted of school principals, teachers, and students from several elementary schools in the Selayar Islands. Data collection techniques were carried out thru observation, interviews, documentation, and questionnaires. The data were analyzed qualitatively and quantitatively to obtain a comprehensive picture of the program's effectiveness. The research results show that the implementation of the School Literacy Movement in elementary schools in the Selayar Islands has been quite successful, especially in the activity of reading for 15 minutes before lessons begin. The support of the principal and teachers has been the main factor in the program's success. However, several obstacles are still found, such as limited reading collections, inadequate library facilities, low parental involvement, and suboptimal use of digital literacy media. From the aspect of results, the GLS program has a positive impact on students' reading interest, reading comprehension skills, and reading habits, although the improvement is not yet uniform across all schools. Based on the evaluation results, there is a need to improve literacy facilities, strengthen collaboration between schools and parents, and provide ongoing training for teachers in the development of innovative literacy activities. Thus, the School Literacy Movement Program in the Selayar Islands is expected to build a sustainable literacy culture and improve the quality of primary education.